Visualization of Critical Limits and Critical Values Facilitates Interpretation - Ania Shah; Jenna Dohner; Kaifeng Cheng; Maria Garcia; Gerald J. Kost (Diagnostics)
Background/Objectives: This study aimed to analyze critical limit and critical value test lists from major US medical centers, identify changes in quantitative critical limit thresholds since 1990, document notification priorities for qualitative and new listings, and visualize information alongside clinical thresholds and pathophysiological trends. Methods: A systematic search was conducted, acquiring 50 lists of critical limits and critical values from university hospitals, Level 1 trauma centers, centers of excellence, and high-performing hospitals across the US. Lists were obtained through direct contact or web-accessible postings. Statistical analysis used the Kruskal–Wallis non-parametric test and Student’s t-test to determine significant differences between 1990 and 2024 critical limits. Results: Statistically significant differences were identified in various clinical tests between 1990 and 2024, comprising glucose, calcium, magnesium, CO2 content, blood gas parameters, hematology, and coagulation tests. Ranges for critical limits narrowed for several tests, and new measurands were added. Cardiac biomarkers were infrequently listed. Point-of-care testing (POCT) listings were sparse and showed significant differences from main lab values in the high median critical limit for glucose Conclusions: Visualizing this information has potential benefits, including ease of interpretation, which can improve patient care, reduce inconsistencies, and enhance the efficiency and quality of healthcare delivery.